The Use Of English Stories Applications In Developing Students' Reading Comprehension - cahyani, cahyani; Syahrir, Syahrir; Puspa sari, Puspa sari (Institut Agama Islam Negeri Palopo, 2023)
This study aims to determine students' understanding of reading skills using the English stories application. The method used in this study was Quasi Experimental Design with 20 students at SMPN 10 Palopo as research subjects. Pretest and posttest techniques to collect data in this study. One of the teaching materials used is a story that is in the application with the theme of fable stories with the title the little mouse. Reading comprehension activities last 15 minutes. After that, students are asked questions about the contents of the story for evaluation using a written test. The results of the study showed that there was an activity to improve reading comprehension skills in class VIII students of SMPN 10 Palopo, as evidenced by the processing of the test results given to students. Thus it can be concluded that using the English stories application can improve students' reading comprehension skills significantly.Keywords: Â English stories,Application,Reading Comprehension